Description of User Satisfaction with “POTENSI” Applications - Fitra Dyna; M. Zul' Irfan; Rizka Febtrina; Wardah Wardah (GLOBAL HEALTH SCIENCE GROUP, 2022)
Nursing students must pass the national nurse competency test (UKOM) in order to be certified as competent nurses and start working as nurses. From year to year, UKNI's graduation rate remains comparatively low. Because of the difficulty with exit exams, health education institutions must be able to give each of their students the best preparation possible for competency exams. The purpose of this study is to gather data on user satisfaction with the potential application. Descriptive analytic research methodology is used here. At STIKes Payung Negeri Pekanbaru, the study was carried out. Students enrolled in the NERS Professional Program in 2020 and 2021 make up the research population. A total of 109 samples were collected using a straightforward random sampling procedure. Questionnaires were employed to gather the data. According to the study's findings, 20 respondents (51.3%) in 2020 and 44 respondents (62.9%) in 2021 expressed a high level of satisfaction with the potential application. This study's conclusion is that students who are prepared for the NERS competency test may find the Potential application useful.